2021
DOI: 10.3389/fpsyt.2021.575147
|View full text |Cite
|
Sign up to set email alerts
|

Yoga as Complementary Care for Young People Placed in Juvenile Institutions—A Study Plan

Abstract: Recent studies have established yoga practice as a mainstream complementary clinical tool within correctional environments. It is shown that regular yoga practice is coupled with improved impulse control, sustained attention, attenuated antisocial and self-harm behaviors, reduced stress, and psychological distress. No academic research until now has provided evidence of mental health benefits of yoga for institutionalized young people. In Sweden, each year more than thousand adolescents receive compulsory care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Proactive aggression that is proactive increases the individual's level of arousal and draws the attention of others. When compared to people with high CFI-Alternatives, they are more likely end up choosing to commit proactive aggression due to a greater focus on short-term positive emotional experiences (Garivani et al, 2021;Kerekes, 2021;Scheinost et al, 2021). Furthermore, although positive emotions do not trigger aggressive behavior (Burgdorf and Panksepp, 2006), the pleasurable experience and the rapid high arousal of aggression may also be an important factor in triggering aggression (Ramírez et al, 2005;Roberton et al, 2012).…”
Section: Moderating Role Of Cognitive Flexibilitymentioning
confidence: 99%
“…Proactive aggression that is proactive increases the individual's level of arousal and draws the attention of others. When compared to people with high CFI-Alternatives, they are more likely end up choosing to commit proactive aggression due to a greater focus on short-term positive emotional experiences (Garivani et al, 2021;Kerekes, 2021;Scheinost et al, 2021). Furthermore, although positive emotions do not trigger aggressive behavior (Burgdorf and Panksepp, 2006), the pleasurable experience and the rapid high arousal of aggression may also be an important factor in triggering aggression (Ramírez et al, 2005;Roberton et al, 2012).…”
Section: Moderating Role Of Cognitive Flexibilitymentioning
confidence: 99%
“…Yoga practice (combined with standard therapy in institutional care) is anticipated to diminish aggression, antisocial behavior, anxiety, depression, and negative affect in institutionalized youth, concurrently enhancing their cognitive flexibility [37]. Yoga mitigates the adverse impact of behavioral disorders on children and adolescents, consequently reducing tendencies toward aggression and violence [38].…”
Section: Advantages and Potential Effects Of Yoga Interventionmentioning
confidence: 99%
“…It is possible that yoga might help improve executive functions, spatial memory scores, strategic planning and the ability to concentrate. It is shown that regular yoga practice is coupled with the improved impulse control, sustained attention, attenuated antisocial and self-harm behaviors, reduced stress, and psychological distress ( 9 ), as well as with the positive impact to concentration, attention and behavior ( 10 ). These improvements may reflect underlying improvements in motor planning, motor speed, and hand steadiness.…”
Section: Introductionmentioning
confidence: 99%